Penguatan Pendidikan Karakter Kepekaan dan Keterampilan Melalui Masa Pengabdian Santri : Studi Kasus di Madrasah Aliyah Nasy’atul Muta’allimin Gapura Timur, Gapura, Sumenep - Matroni, Matroni; Junaidi, Shidqi; Hidayatillah, Yetti; Basri, Hasan; Yanto, Yusri (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
In this research, it will focus on Building Character Education awareness through Student Service Period (MPS) activities at MA Putra Nasy'atul Muta'allimin Gapura Timur, Sumenep Regency. This MPS is an activity to build awareness of character education and social sensitivity as well as students' social participation skills. The Student Service Period is held in order for students to learn directly from the community. This research is a field research (field research) with qualitative form and literature by collecting data, as well as examining references related to the subject being studied, both papers, books, newspapers, journals, peper as well as interviews using an anthropological approach which means doing study the history of the emergence of MPS by looking at the theoretical framework used in analyzing data or facts, which revolves around the problems faced related to the implementation of this MPS activity. The result is that the Santri Service Period is able to build social-community sensitivity, build awareness of the importance of character education from direct experience in society and is able to make students more skilled and independent. Keywords: Education, Character, MPS